Proslavery and sectional thought in the early South, 1740-1829 : an anthology - Young, Jeffrey Robert (Columbia, S.C. : University of South Carolina Press, 2006)
Even then the theorists included in this anthology emphasized the extent to which southern slaveholders' claims to mastery were rooted in a Western moral tradition that reached back to antiquity.
Introduction : a transatlantic perspective on the problem of proslavery thought -- George Whitefield, 1740 -- Alexander Garden, 1740 -- Thomas Bacon, 1749 -- Samuel Davies, 1757 -- William Knox, 1768 -- Petition to the Virginia Assembly, 1785 -- Henry Pattillo, 1787 -- William Graham, 1796 -- Edmund Botsford, 1808 -- William Meade, 1813 -- William Smith, 1818, 1820 -- Richard Furman, 1823 -- Charles Cotesworth Pinckney, 1829.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Slavery -- Southern States -- Justification -- Sources; Southern States -- Intellectual life -- Sources; Sectionalism (U.S.) -- History -- Sources; Slavery and the church -- Southern States -- History -- Sources; Racism -- Southern States -- History -- Sources; Slavery -- Southern States -- History -- 18th century -- Sources; Slavery -- Southern States -- History -- 19th century -- Sources; Southern States -- Politics and government -- To 1775 -- Sources; Southern States -- Politics and government -- 1775-1865 -- Sources; Esclavage -- États-Unis (Sud) -- Justification -- Sources; Racisme -- États-Unis (Sud) -- Histoire -- Sources; États-Unis (Sud) -- Politique et gouvernement -- Jusqu'à 1775 -- Sources; États-Unis (Sud) -- Politique et gouvernement -- 1775-1865 -- Sources; SOCIAL SCIENCE -- Slavery; Sectionalism (United States); Intellectual life; Politics and government; Racism; Slavery; Slavery and the church; Slavery -- Justification; Southern States; États-Unis (sud) -- Politique et gouvernement -- Histoire -- Sources; Esclavage -- États-Unis -- Histoire -- Sources; christianisme -- esclavagisme -- racisme -- regionalisme -- Etats-Unis -- sud -- 1740 -- 1829 -- document; To 1899; History; Sources